Ornithine decarboxylase of the fungal pathogen Colletotrichum higginsianum plays an important role in regulating global metabolic pathways and virulence. (23rd September 2021) - Yan, Yaqin; Tang, Jintian; Yuan, Qinfeng; Liu, Hao; Huang, Junbin; Hsiang, Tom; Bao, Chonglai; Zheng, Lu
Summary: Colletotrichum higginsianum is an important fungal pathogen causing anthracnose disease of cruciferous plants. In this study, we characterized a putative orthologue of yeast SPE1 in C . higginsianum, named ChODC. Deletion mutants of ChODC were defective in hyphal and conidial development. Importantly, deletion of ChODC significantly affected appressorium‐mediated penetration in C . higginsianum . However, polyamines partially restore appressorium function and virulence indicating that loss of ChODC caused significantly decreased virulence by the crosstalk between polyamines and other metabolic pathways. Subsequently, transcriptomic and metabolomic analyses demonstrated that ChODC played an important role in metabolism of various carbon and nitrogen compounds including amino acids, carbohydrates and lipids. Along with these clues, we found deletion of ChODC affected glycogen and lipid metabolism, which were important for conidial storage utilization and functional appressorium formation. Loss of ChODC affected the mTOR signalling pathway via modulation of autophagy. Interestingly, cAMP treatment restored functional appressoria to the Δ ChODC mutant, and rapamycin treatment also stimulated formation of functional appressoria in the Δ ChODC mutant. Overall, ChODC was associated with the polyamine biosynthesis pathway, as a mediator of cAMP and mTOR signalling pathways to regulate appressorium function. Our study provides evidence of a link between ChODC and the cAMP signalling pathway and defines a novel mechanism by which ChODC regulates infection‐associated autophagy and plant infection by fungi.